From Level 5 to Level 3 Lockdown: The Work Experiences and Employment Relationships of Domestic Workers During the COVID-19 Pandemic in South Africa - Zanazo, Zukiswa (Department of Sociology, 2024)
This study explores the work experiences of domestic workers in the Western Cape during levels 5, 4 and 3 of the lockdowns in 2020. The aim of this research was to discover how the lockdowns affected domestic workers' working conditions and employment relationships. The research adopted a qualitative research design that used in-depth, semi-structured interviews with South African and migrant domestic workers. Since this study focused on the employment relationship and working conditions of domestic workers, theoretical concepts such as reproductive labour, boundary work and precarity were used. The study found that the COVID19 pandemic exposed domestic workers to heightened precarity in working arrangements, with employers exercising control over domestic workers' minds, bodies and voices. In terms of the employment relationship, domestic workers experienced personalism with some form of distant hierarchy before the pandemic and experienced distant hierarchy in the form of physical and social distancing during the pandemic, as perceived carriers of COVID-19. In addition, domestic workers experienced control over their minds (uncertainty related to job security and their health), their bodies (limited or no control over decisions regarding COVID-19-related protocols in their workplaces plus intensified workload) and their voices (inability to express grievances regarding working conditions and their right to a safe working environment). This study therefore argues that domestic workers had to endure precarious working conditions because the COVID-19 pandemic exacerbated job insecurity in the domestic sector, making them vulnerable to employers' demands. This study concludes that the longstanding challenge of compliance with legislation and informality in the domestic sector entrenches domestic workers' precariousness. While the majority of employers in this study were partially compliant (for example, granting leave and paying a minimum wage), domestic workers feared losing their jobs because they had never signed an employment contract with their employers nor were registered for UIF. This study advocates that government should devise methods to improve labour regulation in the domestic sector and enforce labour compliance among employers to improve domestic workers' situation, especially against unforeseen economic or health crisis.